Um modelo de otimização para o problema de dimensionamento e programação de lotes de produção em máquina única - Scalcon, Cezaraugusto Gomes (2012)
In this paper we proposed 0-1 integer programming formulation to model single batch processing machine. This problem deals with a set of jobs with non-identical sizes and processing times that has to be grouped to form batches according to the limited capacity of the machine. The processing time of a batch is the longest processing time of all jobs in the batch. The performance measure is the total time required to process all jobs (makespan). The formulation presented strengthens the model, i.e., it is closer to the optimal formulation than those proposed in the literature. Computational experiments demonstrate that the model is consistent and adequately represents the problem addressed.